Applied research of health education based on KAP model in patients with chronic kidney disease in a community - LONG Xiong-chu (Linchuang shenzangbing zazhi)
Objective To explore the application of health education based on the knowledge-attitude-practices(KAP) model in patients with chronic kidney disease(CKD) in a community. Methods With simple random sampling method, 84 patients with CKD were enrolled from the outpatient clinic of Panjiayuan Second Community Health Service Center in Chaoyang District of Beijing. They were divided into observation group(42 cases) and control group(42 cases) according to the order of patient visits. The control group adopted routine health education, and the observation group health education based on the KAP model. Two groups of patients were followed up for 12 months, and the health education effects of the two groups were compared. Results In the observation group 40 patients completed the study, 1 patient lost follow-up, and 1 patient was removed due to incomplete information. In the control group 40 patients completed the study, and 2 ones lost follow-up. Before intervention, there was no statistically significant difference in each item between the two groups. After intervention, understanding of CKD related knowledge, attitude toward CKD prevention, self-management behavior, management and control of CKD progression risk factors and decreased CKD risk stratification in the observation group were significantly higher than those in the control group, with statistically significant difference(P<0.05). Conclusions Health education based on the KAP model can effectively improve patients’ cognitive level of CKD-related knowledge, cultivate correct prevention and self-management behavior, manage high-risk factors of CKD progression, and delay progression of CKD.